2020
DOI: 10.1042/bsr20200800
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA PVT1-mediated miR-543/SERPINI1 axis plays a key role in the regulatory mechanism of ovarian cancer

Abstract: Purpose: To investigate the regulation mechanism of long non-coding RNA (lncRNA) plasmocytoma variant translocation 1 (PVT1) in ovarian cancer (OC). Methods: The levels of PVT1, microRNA (miR)-543, serpin peptidase inhibitor-clade I (neuroserpin)-member 1 (SERPINI1) in OC tissues and OVCAR-3, A2780, TOV-112D of OC cell lines were detected by quantitative real-time PCR (qRT-PCR) and Western Blot (WB). Cell proliferation, migration, invasion, apoptosis and the regulatory relationship between genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
3
12
0
Order By: Relevance
“… 37 lncRNAs PTV1 and PCAT6 act as ceRNAs to sponge miR-543 to regulate SERPINI1 and ZEB1 expression, respectively. 48 , 49 In the present study, we found that FDNCR sponged miR-543-3p to negatively regulate miR-543-3p function in GC proliferation and apoptosis. Alternatively, miR-543-3p promoted GC proliferation, which was consistent with previous studies.…”
Section: Discussionsupporting
confidence: 57%
“… 37 lncRNAs PTV1 and PCAT6 act as ceRNAs to sponge miR-543 to regulate SERPINI1 and ZEB1 expression, respectively. 48 , 49 In the present study, we found that FDNCR sponged miR-543-3p to negatively regulate miR-543-3p function in GC proliferation and apoptosis. Alternatively, miR-543-3p promoted GC proliferation, which was consistent with previous studies.…”
Section: Discussionsupporting
confidence: 57%
“…In numerous studies, lncRNA PVT1 (plasmacytoma variant translocation 1) was upregulated in OvCa cell lines and tissues and involved in the promotion of proliferation, migration, EMT, invasion, and metastasis of OvCa cells ( Table 2 ). It was shown that oncogenic PVT1 interacts with several tumor-suppressive miRNAs, such as miR-133a [ 164 ], miR-214 [ 165 ], miR-140 [ 166 ], and miR-543 [ 167 ]; also, inhibition of suppressor miRNAs is one of the modes to enhance the progression of OvCa. Direct binding of PVT1 to miR-133a was validated via transfections, qRT-PCR, and luciferase reporter assays [ 164 ].…”
Section: Oncogenic Lncrnas As Cernas In Ovarian Cancermentioning
confidence: 99%
“…PVT1 inhibited miR-140 as a miRNA sponge, while transcription of PVT1 was regulated by the transcription factor FOXO4 ( Table 2 ). The lncRNA PVT1 and predicted target SERPINI1 (serpin peptidase inhibitor-clade I (neuroserpin)-member 1) were upregulated in OvCa cell lines and tumor tissues, unlike the downregulated tumor-suppressive miR-543 [ 167 ]. A direct interaction was validated in the PVT1/miR-543/SERPINI1 axis via the dual-luciferase reporter assay [ 167 ].…”
Section: Oncogenic Lncrnas As Cernas In Ovarian Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…For example, CYTOR/LINC00152 acts as a ceRNA of miR-125b to upregulate an antiapoptotic protein MCL1 in A2780 and SKOV3 cells ( Chen et al, 2018 ). PVT1 suppresses apoptosis in OVACAR3 and TOV112D cells by inhibiting miR-543 and increasing a miR-543 target SERPIN1 ( Qu et al, 2020 ). In contrast, MEG3 promotes apoptosis in OVCAR8 and SKOV3 cells by sponging miR-205-5p ( Tao et al, 2020 ).…”
Section: Long Non-coding Rna (Lncrna)mentioning
confidence: 99%